Role of drug-eluting stent on Takayasu arteritis with renal artery stenosis - I Ketut Alit Utamayasa; Mia Puspitasari; Taufiq Hidayat; Mahrus Abdur Rahman (Indonesian Pediatric Society, 2022)
Takayasu arteritis (TA) is defined as granulomatous inflammation of large arteries involving the aorta and its primary branches. Takayasu arteritis with renal artery stenosis (TARAS) is a common cause of pediatric renovascular hypertension. The main purposes of TARAS management are to improve high blood pressure and recover renal function. When general medication fails to improve symptoms, renal revascularization may be attempted. Implantation of a drug-eluting stent (DES) has been used as an alternative strategy for pediatric renal revascularization. Here, we report on a 10-year-old, female, Javanese patient with bilateral TARAS who underwent DES implantation. Her clinical presentation was hypertensive crisis and worsened renal function. Bilateral renal artery DES implantation was performed successfully without complications. The child’s blood pressure was controlled using two anti-hypertensive medications after DES implantation and her renal function recovered. Dual anti-platelet therapy was given to minimize the risk of stent thrombosis.